2021
DOI: 10.1080/1028415x.2021.1889452
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E genotype-dependent nutrigenetic effects to prebiotic inulin for modulating systemic metabolism and neuroprotection in mice via gut-brain axis

Abstract: Objective: The goal of the study was to identify the potential nutrigenetic effects to inulin, a prebiotic fiber, in mice with different human apolipoprotein E (APOE) genetic variants. Specifically, we compared responses to inulin for the potential modulation of the systemic metabolism and neuroprotection via gut-brain axis in mice with human APOE ε3 and ε4 alleles. Method: We performed experiments with young mice expressing the human APOE3 (E3FAD mice and APOE4 gene (E4FAD mice). We fed mice with either inuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
(52 reference statements)
2
12
0
Order By: Relevance
“…Genotype differences may be pronounced during early disease, but the disease course causes both genotypes to exhibit a similar biochemical profile as the disease progresses and neurons are lost. These genotype differences should be further explored to determine whether precision interventions, like the consumption of inulin or the administration of rapamycin, could be implemented for ε4 carriers [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotype differences may be pronounced during early disease, but the disease course causes both genotypes to exhibit a similar biochemical profile as the disease progresses and neurons are lost. These genotype differences should be further explored to determine whether precision interventions, like the consumption of inulin or the administration of rapamycin, could be implemented for ε4 carriers [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, alterations of bile acid production have been observed in AD patients due to gut microbiome imbalances, suggesting another mechanism by which AD patients may benefit from therapeutic strategies aiming to restore normal brain metabolism like the ketogenic diet [ 59 , 60 ]. Another animal study showed that by modulating the gut microbiome with a prebiotic diet, mice with the human APOE ε4 gene had enhanced systemic metabolism and reduced neuroinflammatory gene expression, another hallmark of AD pathology [ 51 , 61 ]. Collectively, modulating metabolic function and the gut microbiome may profoundly impact reducing the risk of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we determined if prebiotic inulin could mitigate injury-induced dysbiosis and restore CBF and WMI by modulating gut microbiome from 3 months post injury (mpi) to 5 mpi. We chose inulin because it consists of non-digestible carbohydrates that can stimulate the growth of bacteria that produce SCFAs [ 14 , 15 ] and enhance neuroprotection [ 16 , 17 ]. We expect the outcomes from the study will advance our knowledge on dysbiosis after CHI from acute to chronic phases, and the potential of dietary intervention for facilitating CHI recovery.…”
Section: Introductionmentioning
confidence: 99%
“…There were differences in the levels of brain metabolites associated with oxidative stress and the expression of claudin-1 and claudin-5 BBB tight junctions. 110 Gut−Kidney Axis. The composition of the intestinal microbiota of patients with chronic kidney disease (CKD) and the mechanism by which the imbalance of the intestinal flora promotes the progression of CKD have been studied to determine possible treatment goals and improve the survival rate of patients with CKD.…”
Section: Journal Ofmentioning
confidence: 99%